PENGEMBANGAN MOTIF PATRA PUNGGEL BALI PADA ROLL CAKE PANGGANG: DEVELOPMENT OF THE BALINESE PATRA PUNGGEL MOTIF ON BAKED ROLLED CAKES - Danty Rosalina Rawas; Luh Masdarini; Ni Wayan Sukerti (Universitas Pendidikan Ganesha, 2026)
This study aims to describe the stages of the patra punggel bali motif on baked roll cake using the 4D model. This type of research is R&D (Research and Development) using the 4D model (define, design, development, disseminate). The respondents in this study were 40 general public. The data collection method used was a questionnaire given to experts and respondents with a Likert scale scoring technique. The data obtained were analyzed using descriptive quantitative techniques. The results showed that the feasibility of the patra punggel bali motif on baked roll cake using the 4D model was categorized as “very feasible”. The feasibility scores were in terms of the visual aesthetic aspect of the motif, which was 3.0 in the very good category, the motif application technique aspect on roll cake was 3.5 in the very good category, the creativity and innovation aspect was 4.0 in the very good category, and the suitability aspect of the motif to the media (roll cake) was 4.0 in the very good category. The public response obtained a score in terms of the motif shape aspect of 3.85 in the very like category, and in terms of the motif color aspect of 3.72 in the very like category. From the results of this study, it can be concluded that the development stages of the patra punggel bali motif on baked roll cake using the 4D model are very feasible as seen from the feasibility of the patra punggel bali motif on baked roll cake being in the very suitable category and the general public response really liking bright colors. The basic colors of the patra punggel motif on roll cake are cream and black for the lines, bright tertiary colors for the patra punggel bali motif throughout the roll cake look very clear. The shape of the patra punggel bali motif is arranged horizontally, neatly, and in perfect shape.